2010
DOI: 10.1136/ip.2010.029215.328
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of severe work-related injuries in Tanzania: call for new approach to workers protection in developing countries

Abstract: BackgroundWork-related injuries affect people in their most productive years. Globally more than 5500 workers are killed by injuries and illnesses every day, and more than 270 million workers are injured at work each year (ILO, 2009).Severe work-related injuries and the resulting adverse socioeconomic impacts, represent a special burden to developing countries. This study, which was conducted in Tanzania, sought to describe patterns of severe traumatic work-related injuries; identify their causes and risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There were three studies focusing specifically on work-related injuries. In 2010, Kishashu et al surveyed 1385 patients with injuries from 2007 to 2008 and found that 638 (46%) were work related [ 25 ]. In 2013, Boniface et al examined 248 miners suffering WRI from 2009 to 2012 and found that 98.7% of workers did not use protective gear and worked over 12 hours daily.…”
Section: Resultsmentioning
confidence: 99%
“…There were three studies focusing specifically on work-related injuries. In 2010, Kishashu et al surveyed 1385 patients with injuries from 2007 to 2008 and found that 638 (46%) were work related [ 25 ]. In 2013, Boniface et al examined 248 miners suffering WRI from 2009 to 2012 and found that 98.7% of workers did not use protective gear and worked over 12 hours daily.…”
Section: Resultsmentioning
confidence: 99%